2011
DOI: 10.1208/s12249-011-9642-x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorph Transformation in Paracetamol Monitored by In-line NIR Spectroscopy During a Cooling Crystallization Process

Abstract: The reliable in-line monitoring of pharmaceutical processes has been regarded as a key tool toward the full implementation of process analytical technology. In this study, near-infrared (NIR) spectroscopy was examined for use as an in-line monitoring method of the paracetamol cooling crystallization process. The drug powder was dissolved in ethanol-based cosolvent at 60°C and was cooled by 1°C/min for crystallization. NIR spectra acquired by in-line measurement were interpreted by principal component analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 20 publications
1
26
0
2
Order By: Relevance
“…12). This finding supports the findings Wang et al [52] for paracetamol where they have studied the impact of cooling on crystallization process.…”
supporting
confidence: 91%
“…12). This finding supports the findings Wang et al [52] for paracetamol where they have studied the impact of cooling on crystallization process.…”
supporting
confidence: 91%
“…The vibrational band due to the SOL in this region was flat indicating that it was not affecting the PMOL vibrational bands. It has been reported in previous NIR studies that the two polymorphs of PMOL (Form I and Form II) exhibit different vibrational band profiles. Similarly, from the data in Figure b, it can be seen that the second derivative NIR spectra showed a significant band shift, notably between 4900 and 4950 cm −1 , indicating that the polymorphic transformation of PMOL from its most stable Form I to the relatively less stable Form II takes place during the HME process at 120°C.…”
Section: Resultsmentioning
confidence: 94%
“…The vibrational band due to the SOL in this region was flat indicating that it was not affecting the PMOL vibrational bands. It has been reported in previous NIR studies 35,36 that the two polymorphs of PMOL (Form I and Form II) exhibit different vibrational band profiles. Similarly, from the data in Figure 5b, it can be seen that the second derivative NIR spectra showed a significant band shift, notably between 4900 and 4950 cm −1 , indicating that the polymorphic transformation of PMOL from its most stable Form I to the relatively less stable Form II takes place during the HME process at 120 • C. From the results obtained, it can be concluded that the band shifts between the NIR spectra of PMOL Form I and the extrudates (PMOL/SOL 40%-60%) support the findings from the VTXRPD data with regard to the predictions of the polymorphic transformation of PMOL (from its Form I to Form II) during HME.…”
Section: In-line Nir Spectroscopy Monitoringmentioning
confidence: 90%
“…The PLS models showed accurate quantification with a high correlation coefficient (0.99) and lower standard errors (1.73%) for crystallinity determination. In addition, several works have been reported for the detection of crystallinity in various pharmaceutical substances such as polymorph A, glycine, paracetamol, miokamycin, and indomethacin using NIR spectroscopy Blanco et al, 2003;Bai et al, 2004;Otsuka et al, 2007;Wang et al, 2011;).…”
Section: Polymorphismmentioning
confidence: 99%